The Colours and Fastness Values obtained from Basil (Ocimum basilicum) and Lemon Balm (Melissa officinalis) Plants of the Lamiciacae Family - Hülya Kaynar; Gülşaj Kütük Dinçel; Aslıhan Gürbüzer; Esra Uçar (International Journal of Secondary Metabolite)
Until the invention of synthetic dye substances, natural dyes were used for the purpose of dyeing in textiles, food, medicine and cosmetics fields. With the introduction of synthetic dyes, their use increased and the demand for natural dyes decreased. However, as a consequence of studies made, the carcinogenic properties of synthetic dyes were revealed and that they could create serious problems for human health. Therefore, plant dyes have come to the fore again. In this study, an examination was made of the dye properties and colour and friction fastness values of basil (Ocimum basilicum) and lemon balm (Melissa officinalis) plants. According to the data obtained, basil and lemon balm dyeing were made with different mordants and different colors were obtained. The highest colour fastness values for basil were seen to be obtained with copper II sulphate, iron II sulphate, potassium bi chromate and citric acid mordants. The highest friction fastness values were obtained with copper II sulphate, potassium aluminium sulphate and citric acid mordants. For the lemon balm, the highest colour fastness values were obtained with all the mordants and the highest friction fastness values with acetic acid and citric acid mordants.